Effect of water storage and thermocycling on light transmission properties, translucency and refractive index of nanofilled flowable composites - Almasabi, Waleed; Tichy, Antonin; Abdou, Ahmed; Hosaka, Keiichi; Nakajima, Masatoshi; Tagami, Junji (Dental materials journal, 2021)
The effect of 1-week water storage and subsequent 10,000 thermal cycles on light transmission properties (straight-line transmission (G0), diffusion (DF), the amount of transmitted light (AV)), translucency parameter (TP) and refractive index (RI) of four nanofilled flowable composites was examined. The composites included Filtek Supreme Ultra Flowable Restorative (FSU), Estelite Flow Quick (EFQ), Estelite Universal Flow, (EUF), and Clearfil Majesty ES Flow (ESF), all of A3 shade. For composites with lower filler load (FSU, EFQ), water storage increased G0, AV and TP, but subsequent thermocycling decreased them. An opposite tendency was found for DF. Materials with higher filler load (EUF, ESF) were not significantly affected by aging conditions. RI of EFQ and EUF containing bisphenol A polyethoxy methacrylate (Bis-MPEPP) increased significantly after thermocycling. Additionally, morphological changes were observed using scanning electron microscopy which revealed cracks within nanocluster fillers and dislocation of particles in FSU and EFQ after thermocycling.
Keywords: testování materiálů; složené pryskyřice; povrchové vlastnosti; voda; Light; Methacrylates; mikroskopie elektronová rastrovací; Materials Testing; Refractometry; světlo; Water; refraktometrie; zubní materiály; Surface Properties; methakryláty; Dental Materials; Microscopy, Electron, Scanning; Composite Resins